Physiotherapeutic treatment in elderly women with urinary incontinence: an integrative literature review (Research, Society and Development, 2023)
Introduction: Urinary Incontinence (UI) is the unexpected loss of urine. It's a problem, which is mistakenly understood to be a normal part of the aging process. Physiotherapy as a form of treatment in UI, will provide improvement and/or cure through education of the voiding function, guidance on the correct use of the pelvic floor muscles, providing the understanding of techniques and exercises for the acquisition of muscle strengthening, its main objective being the re-education of the pelvic floor muscles, as well as its strengthening. Objective: To report the influence of physical therapy as a method of treatment for elderly women with urinary incontinence. Methodology: This is a bibliographic research of the integrative literature review type, carried out by searching the Google Scholar, PEDro and PubMed databases. Results: Seven articles were included in this review, which used physical therapy treatment in elderly women with urinary incontinence. Conclusion: Through the results achieved in this work, physiotherapy is shown to be of fundamental importance in improving or curing the signs and symptoms of patients with urinary incontinence, in which, through techniques and exercises provided by physiotherapy, it also favors the improvement of quality of life.